APPLICATION OF ARTIFICIAL INTELLIGENCE IN THE PROCESS OF LEARNING AND SELF-DEVELOPMENT OF A TEACHER (EDUCATION IN THE 21ST CENTURY, 2025)
One of the most pressing issues studied by modern researchers is the challenge of integrating digital technologies into the educational process.This article explores the potential uses of artificial intelligence in education, analyzing the opportunities and challenges that educational institutions face when integrating AI into teaching and learning processes. Special focus is given to the future prospects of AI in education and its impact on students, teachers, and other stakeholders. Based on the analysis, it is clear that AI has significant potential to enhance learning outcomes and student performance. However, successful integration of this technology will require addressing several key challenges. Additionally, the article examines how teachers can use AI for both educational purposes and personal development, as well as the potential for investment in the educational process.A significant advantage of using artificial intelligence in education is the reduction of time spent on tasks, leading to increased efficiency for teachers. By analyzing data on students' assimilation of educational material, AI systems can provide personalized recommendations that enhance both the efficiency of the educational process and the quality of education. Additionally, AI's ability to automatically analyze large datasets allows teachers to continuously update, improve, and develop instructional content.Artificial intelligence can also help administrators of educational institutions create schedules and determine the most effective educational resources.Experimental studies have proven the hypothesis of the effectiveness of using artificial intelligence in educational activities, but the teacher must have a sufficiently broad outlook, be ready to identify inaccuracies, correct errors, and distribute educational content.
Keywords: educational process; self-development; artificial intelligence; pedagogical professional activity; educational activity; digital tools